Synergies of Fe Single Atoms and Clusters on N‐Doped Carbon Electrocatalyst for pH‐Universal Oxygen Reduction. Issue 5 (10th February 2021) - Liu, Mengjie; Lee, Jeongyeon; Yang, Tsung‐Cheng; Zheng, Fangyuan; Zhao, Jiong; Yang, Chia‐Min; Lee, Lawrence Yoon Suk
Abstract: Single atomic metal–N–C materials have attracted immense interest as promising candidates to replace noble metal‐based electrocatalysts for the oxygen reduction reaction (ORR). The coordination environment of metal–N–C active centers plays a critical role in determining their catalytic activity and durability, however, attention is focused only on the coordination of metal atoms. Herein, Fe single atoms and clusters co‐embedded in N‐doped carbon (Fe/NC) that deliver the synergistic enhancement in pH‐universal ORR catalysis via the four‐electron pathway are reported. Combining a series of experimental and computational analyses, the geometric and electronic structures of catalytic sites in Fe/NC are revealed and the neighboring Fe clusters are shown to weaken the binding energies of the ORR intermediates on Fe–N sites, hence enhancing both catalytic kinetics and thermodynamics. This strategy provides new insights into the understanding of the mechanism of single atom catalysis. Abstract : A pH‐universal electrocatalyst for the oxygen reduction reaction (ORR) is prepared based on Fe single atoms and clusters co‐embedded in N‐doped carbon. The unique single atom/cluster structure and pyridinic‐N‐rich carbon framework of hierarchical porosity enable excellent ORR activity and stability in both alkaline and acidic media, as manifested by high E onset of 0.97 V in base and 0.80 V in acid.